Expression of Nectin-4 in Bladder Urothelial Carcinoma, in Morphologic Variants, and Nonurothelial Histotypes. Issue 8 (September 2021) - Hoffman-Censits, Jean H.; Lombardo, Kara A.; Parimi, Vamsi; Kamanda, Sonia; Choi, Woonyoung; Hahn, Noah M.; McConkey, David J.; McGuire, Bridget M.; Bivalacqua, Trinity J.; Kates, Max; Matoso, Andres
Abstract : The antibody-drug conjugate enfortumab-vedotin acts by targeting nectin-4, a protein that is nearly ubiquitously expressed in conventional urothelial cancer. However, expression of nectin-4 in morphologic variants of urothelial carcinoma and nonurothelial histotypes was unknown. Immunohistochemistry for nectin-4 using was performed on 169 patients including 83 with nonmuscle invasive bladder cancer and 86 patients with muscle invasive bladder cancer. Staining was scored for intensity (0 to 3) and extent (% positive cells) using the histological score system, where >15 was considered positive. Overall, 72/83 (87%) samples of nonmuscle invasive urothelial carcinoma were positive, including 29/30 (97%) noninvasive papillary urothelial carcinomas, 7/8 (87.5%) carcinomas in situ, 36/45 (80%) papillary urothelial carcinomas invading the lamina propria. Overall, 50/86 muscle invasive tumors were positive, including 15/22 (68.2%) urothelial carcinomas, 7/10 (70%) squamous cell carcinomas, 3/11 (28%) micropapillary tumors, 4/6 (66%) adenocarcinomas, 2/4 (50%) nested carcinomas, 5/8 (63%) plasmacytoid, 1/10 (10%) sarcomatoid carcinomas, and 0/15 (0%) small cell carcinomas. Whole transcriptome RNA sequencing revealed that compared with conventional urothelial carcinomas, most sarcomatoid carcinomas and all but 2 small cell carcinomas expressed very low levels of nectin-4 mRNA but expressed significant levels of either trop2 or ERBB2, which are the molecular targets of 2 other antibody-drug conjugates—sacituzumab gavitecan (trop2) or trastuzumab deruxtecan (ERBB2/HER2). In summary, our study demonstrates that there is heterogeneity of expression of nectin-4 in morphologic variants of urothelial cancer and nonurothelial histotypes, and suggests that testing expression of nectin-4 should be considered in morphologic variants or nonurothelial histotypes found to have lower expression.